2014
DOI: 10.4161/psb.27931
|View full text |Cite
|
Sign up to set email alerts
|

Importance of symplasmic communication in cell differentiation

Abstract: Symplasmic communication via plasmodesmata (PD) is part of the system of information exchange between plant cells. Molecules that pass through the PD include ions, some hormones, minerals, amino acids, and sugars but also proteins, transcription factors, and different classes of RNA, and as such PD can participate in the coordination of plant growth and development. This review summarizes the current literature on this subject and the role of PD in signal exchange, the importance of symplasmic communication an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 102 publications
0
17
0
Order By: Relevance
“…between neighboring cells during plant cell differentiation (Marzec and Kurczynska, 2014). In wild-type barley, symplasmic communication is limited to the root zone in which cells start to develop, whereas in the root-hairless mutant rhl1.b, all epidermal cells, even those in the mature zone of the root, remain interconnected; the absence of callose deposits in the plasmodesmata has been suggested as the basis for this difference (Marzec et al, 2014b).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…between neighboring cells during plant cell differentiation (Marzec and Kurczynska, 2014). In wild-type barley, symplasmic communication is limited to the root zone in which cells start to develop, whereas in the root-hairless mutant rhl1.b, all epidermal cells, even those in the mature zone of the root, remain interconnected; the absence of callose deposits in the plasmodesmata has been suggested as the basis for this difference (Marzec et al, 2014b).…”
Section: +mentioning
confidence: 99%
“…The indications are that any enhancement in RH function may offer a potential route to improving the productivity and stress tolerance of crops that are grown in poor soils (Meister et al, 2014). Last, but not least, the root epidermis of grass species represents a useful model for cell differentiation (Marzec and Kurczynska, 2014).…”
Section: +mentioning
confidence: 99%
“…The SE efficiency of internode explants was significantly improved by short-term treatment (up to 1 h) with sucrose. There is evidence in the literature to support the hypothesis that osmotic treatment may enhance somatic embryo production in two ways: it may cause selection of certain cell types, as shown for osmotically dehydrated embryogenic tissue of Gentiana cruciata, G. kurroo (Mikuła et al 2011a, b) and Pinus sylvestris (Häggman et al 1998), or alternatively, severe but non-fatal stress treatment may lead to the symplasmic isolation of cells (Marzec and Kurczynska 2014). It was demonstrated that disruption of plasmodesmata between explant cells promotes the somatic-toembryogenic transition (Verdeil et al 2001;You et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The shorter cells contained a denser cytoplasm, a greater number of mitochondria and only this type of cells produced root hair tubes 15 . Differentiation of both cell types is correlated with the restriction of symplasmic communication between neighboring cells 19 , 26 …”
mentioning
confidence: 99%